PERAN GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM MEMBINA AKHLAK SISWA SMP NEGERI 3 SURUH, KABUPATEN SEMARANG TAHUN AJARAN 2024 /2025 - Mardhiyah Agung Wahyuningsih (STKIP Pesisir Selatan, 2026)
The widespread moral degradation in schools is slowly becoming a major obstacle to the continuity of learning and achieving educational goals. Creating a generation with character, competence, and morals will be difficult to achieve. This problem certainly requires a more significant role for teachers to address. Therefore, this study aims to describe the role of Islamic Religious Education and Character Building teachers in fostering the morals of eighth-grade students at SMP Negeri 3 Suruh, Semarang Regency. A qualitative approach was used, with data collection methods including observation, interviews, and documentation. Data reduction and triangulation were used as analysis techniques. The results indicate that Islamic Religious Education teachers play the role of correctors, inspirators, informants, motivators, and guides. Guidance efforts are carried out through role models, habituation, advice, and educational punishment. Supporting factors include collaboration between teachers and parents, while the main inhibiting factors are students' lack of awareness and the influence of their social environment. This study emphasizes the role and contribution of Islamic Religious Education and Character Building teachers in fostering students' character and good morals.